A novel approach for the modelling of air quality dynamics in underground railway stations. (October 2017) - Walther, E.; Bogdan, M.
Highlights: Proposal of a model for train related air quality. Comparison between model and PM10 measurements of 4 underground stations. Determination of an apparent emission term. Abstract: Indoor air quality in subterranean train stations is a concern in many places around the globe. However, due to the specificity of each case, numerous parameters of the problem remain unknown, such as the braking discs particle emission rate, the ventilation rate of the station or the complete particle size distribution of the emitted particles. In this study the problem of modelling PM10 concentration evolution in relation with train traffic is hence addressed with a particle-mass conservation model which parameters are fitted using a genetic algorithm. The parameters of the model allow to reproduce the dynamics and amplitude of four field data sets from the French and Swedish underground contexts and comply with realistic bounds in terms of emissions, deposition and ventilation rate.